Deje $A(0,a),B(b,0),C(c,0),M(x_1,y_1)$
$k_{AM}=\dfrac{y_1-a}{x_1},A_0M: y-y_1=\dfrac{x_1}{a-y_1}(x-x_1) \to A_0 \left(\dfrac{x_1^2+y_1^2-ay_1}{x_1},0\right)$
$k_{BM}=\dfrac{y_1}{x_1-b},B_0M:y-y_1=-\dfrac{x_1-b}{y_1}(x-x_1),AC:y=-\dfrac{a}{c}(x-c) \to B_0 \left(\dfrac{c(y_1^2+x_1^2-ay_1-bx_1)}{cx_1-ay_1-bc},-\dfrac{a(y_1^2+x_1^2-cx_1-bx_1-bc)}{cx_1-ay_1-bc} \right)$
$k_{cM}=\dfrac{y_1}{x_1-c},C_0M:y-y_1=-\dfrac{x_1-c}{y_1}(x-x_1),AB:y=-\dfrac{a}{b}(x-b) \to C_0 \left(\dfrac{-b(y_1^2+x_1^2-ay_1-cx_1)}{bx_1-ay_1-bc},-\dfrac{a(y_1^2+x_1^2-bx_1-cx_1-bc)}{bx_1-ay_1-bc} \right)$
$k_{A_0B_0}=\dfrac{\dfrac{a(y_1^2+x_1^2-cx_1-bx_1-bc)}{cx_1-ay_1-bc}}{\dfrac{x_1^2+y_1^2-ay_1}{x_1}-\dfrac{c(y_1^2+x_1^2-ay_1-bx_1)}{cx_1-ay_1-bc}}=\dfrac{ax_1(y_1^2+x_1^2-cx_1-bx_1-bc)}{y_1(a^2y_1+abc-ax_1^2-ay_1^2-bcy_1)}$
$k_{A_0C_0}=\dfrac{\dfrac{a(y_1^2+x_1^2-cx_1-bx_1-bc)}{bx_1-ay_1-bc}}{\dfrac{x_1^2+y_1^2-ay_1}{x_1}-\dfrac{b(y_1^2+x_1^2-ay_1-cx_1)}{bx_1-ay_1-bc}}=\dfrac{ax_1(y_1^2+x_1^2-cx_1-bx_1-bc)}{y_1(a^2y_1+abc-ax_1^2-ay_1^2-bcy_1)}$
$k_{A_0B_0}=k_{A_0C_0} \implies A_0,B_0 ,C_0 $ co-line .
Por CIERTO, a mediados de los puntos de $AA_0,BB_0,CC_0$ son también co-line.